Facing the Limits of the Law - Claes, Erik; Devroe, Wouter; Keirsbilck, Bert (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Many legal experts no longer share an unbounded trust in the potential of law to govern society efficiently and responsibly. They often experience the 'limits of the law', as they are confronted with striking inadequacies in their legal toolbox, with inner inconsistencies of the law, with problems of enforcement and obedience, and with undesired side-effects, and so on. The contributors to this book engage in the challenging task of making sense of this experience. Against the background of broader cultural transformations (such as globalisation, new technologies, individualism and cultural diversity), they revisit a wide range of areas of the law and map different types of limits in relation to some basic functions and characteristics of the law. Additionally, they offer a set of strategies to manage justifiably law's limits, such as dedramatising law's limits, conceptual refinement ('constructivism'), striking the right balance between different functions of the law, seeking for complementarity between law and other social practices.